Prodrug suicide gene therapy for cancer targeted intracellular by mesenchymal stem cell exosomes - Altanerova, Ursula; Jakubechova, Jana; Benejova, Katarina; Priscakova, Petra; Pesta, Martin; Pitule, Pavel; Topolcan, Ondrej; Kausitz, Juraj; Zduriencikova, Martina; Repiska, Vanda; Altaner, Cestmir (International journal of cancer, 2019)
The natural behavior of mesenchymal stem cells (MSCs) and their exosomes in targeting tumors is a promising approach for curative therapy. Human tumor tropic mesenchymal stem cells (MSCs) isolated from various tissues and MSCs engineered to express the yeast cytosine deaminase::uracil phosphoribosyl transferase suicide fusion gene (yCD::UPRT-MSCs) released exosomes in conditional medium (CM). Exosomes from all tissue specific yCD::UPRT-MSCs contained mRNA of the suicide gene in the exosome's cargo. When the CM was applied to tumor cells, the exosomes were internalized by recipient tumor cells and in the presence of the prodrug 5-fluorocytosine (5-FC) effectively triggered dose-dependent tumor cell death by endocytosed exosomes via an intracellular conversion of the prodrug 5-FC to 5-fluorouracil. Exosomes were found to be responsible for the tumor inhibitory activity. The presence of microRNAs in exosomes produced from naive MSCs and from suicide gene transduced MSCs did not differ significantly. MicroRNAs from yCD::UPRT-MSCs were not associated with therapeutic effect. MSC suicide gene exosomes represent a new class of tumor cell targeting drug acting intracellular with curative potential.
Keywords: Flucytosine; flucytosin; nádorové buněčné linie; cytosindeaminasa; Breast Neoplasms; Antimetabolites, Antineoplastic; Genes, Transgenic, Suicide; exozómy; Genetic Therapy; kvasinky; suicide gene; Pentosyltransferases; fluoruracil; Fluorouracil; genetická terapie; pentosyltransferasy; Cell Proliferation; protinádorové antimetabolity; Cell Line, Tumor; Mesenchymal Stem Cells; fungální proteiny; MSC suicide gene exosomes; Gene directed enzyme prodrug therapy; mezenchymální kmenové buňky; Prodrugs; Yeasts; Fungal Proteins; Humans; prekurzory léčiv; Exosomes; proliferace buněk; nádory prsu; mesenchymal stem cells; transgeny sebevražedné; lidé; Cytosine Deaminase